Banking on bees - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Thousands of small farmers in African, Caribbean and Pacific countries are keeping bees and making them work hard to improve their living standards. Bees thrive almost everywhere in the ACP countries, and are valuable both for their own products,...